Surface treatment plastic film
Patent Information
- Application Number
- JP2024216419
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2041-04-01
AI Technical Summary
【0009】 本発明の表面処理プラスチックフィルムは、従来のフィルムと比較して、トナー定着性が良く、トナー転写が発生せず、捺印用途も適用できる。更に、手触りにより、別種のプラスチックカードと識別が可能である。
Smart Images

Figure 2025028136000001 
Figure 2025028136000002 
Figure 2025028136000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a surface-treated plastic film. In particular, the present invention relates to a plastic film useful for various labels, cards, delivery slips, recording paper for printers, etc., which has dramatically improved suitability for stamping and writability, and is free of powder falling phenomenon. [Background technology]
[0002] Compared to natural paper, plastic films are superior in water resistance, moisture absorption dimensional stability, flatness, gloss and clarity of printed matter, and mechanical strength, etc., and therefore have come to be widely used as synthetic paper to replace natural paper in fields such as packaging paper, labels, maps, posters, various cards such as business cards, delivery slips, and recording paper for various printers.
[0003] In recent years, electrophotographic printing has become more common due to its simplicity and the improvement in image quality of printed matter. In electrophotographic printing, printing is performed by transferring and fixing fine particles called toner, which are resin particles dispersed with pigments and various additives, onto a film, and in this case, the fixability of the toner to the film is important.
[0004] For example, Patent Document 1 discloses a surface-treated plastic film having a toner-adhesive layer on a substrate. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2003-345051 A Summary of the Invention [Problem to be solved by the invention]
[0006] However, the surface-treated plastic film shown in Patent Document 1 tends to have low surface roughness. In addition, in recent years, as printing and printing speeds have increased, when sheets or continuous sheets are folded and the printed surfaces come into contact with each other, the toner is transferred to the opposing surface due to impact such as friction, which is a problem known as toner transfer. For example, when a surface-treated plastic film such as that shown in Patent Document 1 is used and the printed surfaces come into contact with each other after folding, there is a risk of toner transfer occurring. Furthermore, in recent years, there has been a demand for printability on plastic films in order to replace paper. When stamping on a surface-treated plastic film such as that described in Patent Document 1, there is a risk that the characters will bleed over time and be crushed when rubbed with a finger or an object. In addition, plastic films are required to have characteristics that distinguish them from other plastic films depending on their applications.
[0007] The present invention has been made in consideration of the above-mentioned situation, and aims to provide a surface-treated plastic film that has good toner fixing properties, does not cause toner transfer, can be used for stamping, and can be distinguished from other types of plastic cards by touch. [Means for solving the problem]
[0008] That is, the present invention comprises the following: [1] A surface-treated plastic film having a surface coating layer formed on at least one surface of a substrate plastic film, the surface coating layer is a layer formed by curing a surface coating layer-forming composition containing at least a binder composition (A) and inorganic particles (B); The content of inorganic particles (B) in 100% by mass of the total solid content of the surface coating layer-forming composition is 20% by mass or more and 40% by mass or less; The static friction coefficient (μs) when the surface coating layers are rubbed against each other is 0.65 or less, A surface-treated plastic film, wherein the surface roughness (Ra) of the surface coating layer is greater than 1.6 μm and less than 4.0 μm, and the maximum projection height (Rz) is greater than 20 μm and less than 40 μm. [2] In one embodiment, the surface-treated plastic film contains a wax component as an additive in an amount of 0 mass % or more and 10.0 mass % or less based on the total solid content of the surface coating layer-forming composition that forms the surface coating layer. [3] In one embodiment, the surface-treated plastic film has a binder composition (A) that contains at least a polyester resin, and the content of the polyester resin in 100% by weight of the total solid content of the binder composition (A) is 25% by mass or more and 100% by mass or less. [4] In one embodiment, the surface-treated plastic film has inorganic particles (B) that include at least particles (B1) having an average particle size of 0.1 μm or more and less than 5.0 μm and particles (B2) having an average particle size of 5.0 μm or more and 20.0 μm or less, The mass ratio of B1:B2 is 60:40 to 10:90. [5] In one embodiment, the surface-treated plastic film has a base plastic film that is a polyester film. [6] In one embodiment, the surface-treated plastic film is a substrate plastic film that is a white polyester film containing cavities. [7] In one embodiment, the surface-treated plastic film has a base plastic film which is a polyester film or a white polyester film containing voids, and contains 25% by mass or more and 90% by mass or less of polyester resin made from recycled raw materials such as film scraps and PET bottles relative to the total polyester resin constituting the polyester film or the white polyester film containing voids. Effect of the Invention
[0009] The surface-treated plastic film of the present invention has better toner fixing property than conventional films, does not cause toner transfer, can be used for imprinting, and can be distinguished from other kinds of plastic cards by touch. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The present invention will be described in detail below. (Base plastic film) In the present invention, the plastic film constituting the substrate film may be, for example, various polymer films made of polyolefin, polyester, polyamide, polyimide, polycarbonate, polystyrene, polymethacrylate, polyvinyl chloride, etc., and among these, polyester films are particularly preferred in terms of heat resistance, strength, stiffness, etc. There are no particular limitations on the thickness of these substrate films, but in order to ensure general strength characteristics as synthetic paper, etc., the thickness is preferably 1 to 500 μm, more preferably 10 to 300 μm.
[0011] In the polyesters suitable for use as the base film material, the polyester resins that are the main components are polymers synthesized from dicarboxylic acids or their ester-forming derivatives and diols or their ester-forming derivatives. Representative examples of such polyester resins include polyethylene terephthalate, polybutylene terephthalate, polytrimethylene terephthalate, and polyethylene-2,6-naphthalate, with polyethylene terephthalate being preferred from the standpoints of mechanical properties, heat resistance, cost, etc.
[0012] In addition, these polyester resins may be copolymerized with other components as long as the object of the present invention is not impaired. Specifically, the copolymerization components include dicarboxylic acid components such as isophthalic acid, naphthalenedicarboxylic acid, 4,4-diphenyldicarboxylic acid, adipic acid, sebacic acid and their ester-forming derivatives. In addition, the diol components include diethylene glycol, hexamethylene glycol, neopentyl glycol, and cyclohexanedimethanol. In addition, polyoxyalkylene glycols such as polyethylene glycol and polypropylene glycol are also included. The copolymerization amount is preferably within 10 mol% per constituent repeating unit, more preferably within 5 mol%.
[0013] The polyester resin of the present invention can be produced by, for example, first carrying out an esterification or transesterification reaction using the above-mentioned dicarboxylic acid or its ester-forming derivative and the diol or its ester-forming derivative as main starting materials in a conventional manner, and then carrying out a polycondensation reaction at high temperature and reduced pressure.
[0014] The intrinsic viscosity of the polyester resin pellets of the present invention is preferably in the range of 0.50 to 0.9 dl / g, more preferably in the range of 0.55 to 0.85 dl / g. Such a limiting viscosity improves film formability and recyclability, and is preferable for facilitating stable film production.
[0015] The polyester resin in the present invention may contain polyester resin recycled from PET bottles. The crystallinity of the polyester used in PET bottles is controlled in order to improve the bottle moldability and appearance. As a result, polyester resins containing 0.5 mol% to 10.0 mol% of isophthalic acid components and ester constituent units derived from any diol component represented by ethylene glycol or diethylene glycol relative to the total ester constituent units in the polyester resin may be used. In addition, polyesters with increased intrinsic viscosity may be used by further performing solid phase polymerization after liquid phase polymerization. Polyester resin pellets recycled from PET bottles are usually obtained by washing, crushing, heating and melting the PET bottles to repelletize them, but those with increased intrinsic viscosity by further performing solid phase polymerization may also be used. The intrinsic viscosity of the polyester resin recycled from PET bottles is preferably in the range of 0.60 to 0.75 dl / g. When the intrinsic viscosity is 0.60 dl / g or more, the obtained film is less likely to break, and film production can be stably operated. On the other hand, when the intrinsic viscosity is 0.75 dl / g or less, the filtration pressure of the molten fluid does not increase too much, and film production can be stably operated. In general, when polyethylene terephthalate resin is solid-phase polymerized, the amount of oligomers contained in the resin, especially PET cyclic trimers, which have the highest content, is less than that of the resin polymerized in liquid phase. The upper limit of the cyclic trimer oligomer contained in the polyester resin recycled from PET bottles is preferably 0.7% by mass, more preferably 0.5% by mass, and more preferably 0.4% by mass.
[0016] In one embodiment, the base plastic film is a polyester film or a polyester film containing voids, and can contain 25% by mass or more and 90% by mass or less of polyester resin made from recycled raw materials such as film scraps and PET bottles relative to the total polyester resin constituting the polyester film or the white polyester film containing voids. For example, the polyester film containing voids may be a white polyester film. In one embodiment, the content of polyester resin recycled from PET bottles and polyester resin consisting of film scraps in the void-containing polyester film is preferably 25% by mass or more, more preferably 30% by mass or more, and even more preferably 50% by mass or more, based on the total polyester resin constituting the polyester film. If it is 25% by mass or more, the oligomer contained in the void-containing polyester film is reduced, and precipitation of the oligomer can be suppressed, which is preferable. Furthermore, in terms of utilizing recycled resins, a high content is preferable in terms of contributing to reducing environmental load. The content of polyester resin recycled from PET bottles is preferably 90% by mass or less, more preferably 85% by mass or less.
[0017] The surface-treated film of the present invention obtained by applying the above-mentioned surface coating to at least one side of the above-mentioned substrate film may use a white polyester film as the substrate film in order to enhance suitability as synthetic paper. In this case, the light transmittance is preferably 30% or less, more preferably 20% or less, and even more preferably 15% or less. If the light transmittance is 30% or less, the back side is not visible, and there is no risk of impairing the appearance after printing, which is preferable.
[0018] Furthermore, when a polyester film is selected and used as a base material, a material containing polyester and one or more thermoplastic resins incompatible with the polyester is used as the film material, and the material is stretched at least uniaxially after being formed into a film, and preferably stretched biaxially in the longitudinal and transverse directions to form a large number of fine cavities inside the film and make the apparent specific gravity 0.8 to 1.3, which is extremely suitable as a base film. Of course, a white polyester film and a void-containing polyester film are particularly preferred.
[0019] That is, the thermoplastic resin incompatible with polyester used in this case is blended as a cavity generating agent to form fine cavities in the polyester film to improve flexibility, lightness, and drawability, and can be used without any particular restrictions as long as it is incompatible with polyester, and examples thereof include polystyrene resins, polyolefin resins, cyclic polyolefin resins, polyacrylic resins, polycarbonate resins, and polysulfone resins, among which polystyrene resins or polyolefin resins such as polymethylpentene and polypropylene are particularly preferred. The amount of these incompatible resins blended with polyester varies depending on the target amount of cavities to be formed in the base film, but is generally in the range of 3 to 40 mass% in terms of the ratio in the film material, and particularly preferably 5 to 15 mass%. If it is 3 mass% or more, the effect of forming cavities becomes significant, and the flexibility, lightness, or drawability given to the base film by the formation of cavities is improved, which is preferable. On the other hand, if it is 40 mass% or less, there is no risk of impairing the stretchability of the film, and heat resistance, strength, and stiffness are maintained, which is preferable. The cavity generating agents may be used alone or in combination of two or more kinds.
[0020] The void-containing film as described above preferably has an apparent specific gravity in the range of 0.8 to 1.3, more preferably 1.0 to 1.25, and even more preferably 1.05 to 1.25. If the apparent specific gravity is 0.8 or more, the strength of the film is maintained and there is no risk of cracks or wrinkles on the surface of the film, which is preferable. On the other hand, if the apparent specific gravity is 1.3 or less, cushioning properties are maintained and drawing properties with a pencil or the like are also good, which is preferable.
[0021] In the present invention, the above-mentioned microvoid-containing polyester film preferably used as the substrate film may be a single-layer film, or may of course be a composite film of two or more layers depending on the application.
[0022] In order to improve the hiding power, inorganic or organic particles may be added to the base film as necessary. Examples of particles that can be added include silica, kaolinite, talc, calcium carbonate, zeolite, alumina, barium sulfate, carbon black, zinc oxide, titanium oxide, and organic particles such as benzoguanamine particles, crosslinked polystyrene particles, and crosslinked acrylic particles. The method for producing the plastic film according to the present invention is not particularly limited, but most generally, an oriented film obtained by a biaxial stretching method can be preferably used. That is, an unstretched plastic sheet obtained by a melt extrusion method is stretched 2 to 10 times in the longitudinal direction, and then further stretched 2 to 10 times in the perpendicular direction, and then heat-treated to complete the orientation and crystallization.
[0023] A corona treatment layer or an easy-adhesion layer may be provided on the surface of the base film in order to enhance adhesion with the surface coating layer. Coating methods are generally used to form the easy-adhesion layer, and specifically, gravure coating, kiss coating, dip coating, spray coating, curtain coating, air knife coating, blade coating, reverse roll coating, etc. may be adopted. As for the timing of coating, any method may be adopted, such as a method of coating before stretching the film, a method of coating after longitudinal stretching, or a method of coating on the surface of the film after the orientation treatment, but the most preferable method for enhancing the adhesion of the coating layer is an in-line coating method in which a coating liquid is applied to at least one side of the base film stretched in the uniaxial direction by the above-mentioned coating method, and then the film is further stretched in a direction perpendicular to the previous uniaxial stretching method.
[0024] The resin used in the easy-adhesion layer is not particularly limited, but preferably contains one, two, or three of acrylic, polyester, and urethane compositions. If necessary, the coating composition for the easy-adhesion layer may contain a crosslinking agent.
[0025] (Surface coating layer) The present invention is a surface-treated plastic film having a surface coating layer formed on at least one side of a base plastic film, the surface coating layer being a layer formed by hardening a surface coating layer-forming composition containing at least a binder composition (A) and inorganic particles (B), the content of inorganic particles (B) in 100 mass% of the total solids content of the surface coating layer-forming composition that forms the surface coating layer being 20 mass% or more and 40 mass% or less, the static friction coefficient (μs) when the surface coating layers are rubbed against each other is 0.65 or less, the surface roughness (Ra) of the surface coating layer is more than 1.6 μm and less than 4.0 μm, and the maximum projection height (Rz) is more than 20 μm and less than 40 μm.
[0026] (Binder Composition (A)) Examples of the binder composition (A) used in the present invention include polyester resin, acrylic resin, urethane resin, melamine resin, and styrene resin. Mixtures of these resins with other resins can also be used. For example, other resins include polyvinyl alcohol, which is effective in improving the dispersibility of particles and adhesion to resin. Considering the dispersibility of particles in the surface coating layer and adhesion to resin, polyester resin is preferably used as the binder composition.
[0027] From the viewpoint of increasing the surface hardness of the surface coating layer, preferred binder compositions (A) include acrylic resins, urethane resins and melamine compounds, with urethane resins and melamine compounds being particularly preferred, and melamine compounds being most preferred.
[0028] The polyester resin may be a straight-chain one, but is more preferably a polyester resin composed of a dicarboxylic acid and a diol having a branched structure. The dicarboxylic acid referred to here includes aliphatic dicarboxylic acids such as adipic acid and sebacic acid, and aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, phthalic acid, and 2,6-naphthalenedicarboxylic acid, as well as terephthalic acid, isophthalic acid, phthalic acid, and 2,6-naphthalenedicarboxylic acid. The branched glycol is a diol having a branched alkyl group, and examples thereof include 2,2-dimethyl-1,3-propanediol, 2-methyl-2-ethyl-1,3-propanediol, 2-methyl-2-butyl-1,3-propanediol, 2-methyl-2-propyl-1,3-propanediol, 2-methyl-2-isopropyl-1,3-propanediol, 2-methyl-2-n-hexyl-1,3-propanediol, 2,2-diethyl-1,3-propanediol, 2-ethyl-2-n-butyl-1,3-propanediol, 2-ethyl-2-n-hexyl-1,3-propanediol, 2,2-di-n-butyl-1,3-propanediol, 2-n-butyl-2-propyl-1,3-propanediol, and 2,2-di-n-hexyl-1,3-propanediol.
[0029] It can be said that the polyester resin contains the branched glycol component, which is a more preferred embodiment of the above, in the total glycol components at a ratio of preferably 10 mol % or more, more preferably 20 mol % or more. If it is 10 mol % or less, the crystallinity becomes high and the adhesiveness of the coating layer may decrease. The upper limit of the glycol component in the total glycol components is preferably 80 mol % or less, more preferably 70 mass %. If it is 80 mol % or more, the concentration of oligomers, which are by-products, increases and the transparency of the coating layer may be affected. As the glycol component other than the above compounds, ethylene glycol is the most preferred. If it is a small amount, diethylene glycol, propylene glycol, butanediol, hexanediol, 1,4-cyclohexanedimethanol, etc. may be used.
[0030] The dicarboxylic acid as a component of the polyester resin is most preferably terephthalic acid or isophthalic acid. In addition to the dicarboxylic acid, in order to impart water dispersibility to the copolymerized polyester resin, it is preferable to copolymerize 5-sulfoisophthalic acid or the like in the range of 1 to 10 mol%, for example, sulfoterephthalic acid, 5-sulfoisophthalic acid, 5-sodium sulfoisophthalic acid, etc. A polyester resin containing a dicarboxylic acid having a naphthalene skeleton may be used, but in order to suppress a decrease in adhesion to ink, the quantitative ratio is preferably 5 mol% or less in the total carboxylic acid components, and it may not be used.
[0031] Examples of acrylic resins include those having a hydroxyl group, a methylol group, an ethylol group, a butyrol group, an alkoxymethyl group, an alkoxyethyl group, an alkoxybutyl group, an epoxy group, an imino group, or the like in the main chain and / or side chain, but are not limited to these.
[0032] Examples of urethane resins include various polyurethane resins, polyurethane polyurea resins, and prepolymers thereof. Specific examples of such urethane resins include reaction products of diisocyanate components such as tolylene diisocyanate, xylene diisocyanate, diphenylmethane diisocyanate, hexamethylene diisocyanate, cyclohexane diisocyanate, isophorone diisocyanate, and dicyclohexyl diisocyanate with diol components such as ethylene glycol, propylene glycol, 1,4-butanediol, 1,6-hexanediol, neopentyl glycol, cyclohexane dimethanol, bisphenol, polyester diol, polyether diol, polycarbonate diol, and polyethylene glycol, and reaction products of urethane prepolymers having isocyanate groups at their ends with amino compounds, aminosulfonates, polyhydroxycarboxylic acids, and bisulfites. It is also possible to use a catalyst to increase reactivity.
[0033] The melamine compound is a compound having a melamine skeleton in the compound, and for example, an alkylolated melamine derivative, a compound partially or completely etherified by reacting an alcohol with an alkylolated melamine derivative, and a mixture thereof can be used. As the alcohol used for etherification, methyl alcohol, ethyl alcohol, isopropyl alcohol, n-butanol, isobutanol, etc. are preferably used. In addition, the melamine compound may be either a monomer or a dimer or higher polymer, or a mixture thereof may be used. Furthermore, a product obtained by co-condensing a part of melamine with urea or the like can also be used, and a catalyst can also be used to increase the reactivity of the melamine compound.
[0034] The content of the binder composition (A) is preferably 40% by mass or more and 75% by mass or less, based on 100% by mass of the total solid content of the surface coating layer forming composition forming the surface coating layer. More preferably, it is 45% by mass or more and 70% by mass or less. When it is 40% by mass or more, there is no risk of the inorganic particles falling off, and the static friction coefficient can be reduced, which is preferable. When it is 45% by mass or more, the static friction coefficient can be further reduced, and the transfer of the toner can be prevented, which is preferable. When it is 75% by mass or less, the inorganic particle component is not covered too much, and bleeding and rubbing of the stamp are improved, which is preferable. When it is 70% by mass or less, the coverage of the particle component is further suppressed, and bleeding and rubbing of the stamp are improved, which is even more preferable.
[0035] The content of the polyester resin as the binder composition (A) may not be used at all, but it is preferably 25% by mass or more and 100% by mass or less of the total solid content of the binder composition (A). More preferably, it is 50% by mass or more and 100% by mass or less. If the content of the polyester resin is 25% or more, the toner fixing property after printing tends to be improved. If it is 50% by mass or more, the toner fixing property is further improved, and it can be used for a long time after printing without reprinting.
[0036] (Inorganic particles (B)) In the present invention, examples of inorganic particles (B) used in the surface coating layer include, but are not limited to, silica, kaolinite, talc, calcium carbonate, zeolite, alumina, barium sulfate, carbon black, zinc oxide, and titanium oxide. Among these, silica and calcium carbonate are particularly preferred. It is preferable to combine these inorganic particles with particles (B1) having an average particle size of 0.1 μm or more and less than 5.0 μm and particles (B2) having an average particle size of 5.0 μm or more and 20.0 μm or less. More preferably, inorganic particles B1 are particles having an average particle size of 1.0 μm or more and less than 4.0 μm, and inorganic particles B2 are particles having an average particle size of 7.5 μm or more and 18.0 μm or less, for example, inorganic particles B2 are particles having an average particle size of 9.0 μm or more and 18.0 μm or less. If the average particle diameter of the inorganic particles B1 is 0.1 μm or more, even when the ratio of the inorganic particles described later is 20% by mass, the inorganic particles are not too embedded in the resin, and the surface roughness can be adjusted to a desired range. If the average particle diameter is less than 5.0 μm, the particle diameter is appropriate for forming small irregularities that suppress imprint bleeding, and is preferable. If the average particle diameter of the inorganic particles B2 is 5.0 μm or more, the maximum surface protrusion can be adjusted to a desired range, and the imprint rubbing and toner transfer evaluation are improved, which is preferable. If the average particle diameter of the inorganic particles B2 is 7.5 μm or more, the maximum surface protrusion height is further increased, the above effects are improved, and the surface of the surface coating layer can be made rough to the touch, which is even more preferable. If the average particle diameter is 20 μm or less, the particles can be prevented from falling off the surface coating layer, and heat transfer can be firmly performed to the resin surface when the printing toner is fixed, which is preferable.
[0037] The mass ratio of inorganic particles B1 and B2 is preferably B1:B2=60:40 to 10:90. When the ratio of B1 is 10 or more, the small irregularities bind the imprinting ink, and the occurrence of imprint bleeding can be suppressed. When the ratio is 60 or less, the particles that scrape off the toner do not become too many, and toner transfer can be maintained at a good level. If the ratio of B2 is 40 or more, the particles with a larger particle size will be the contact surface with the opposing toner, and the contact area between the toner and the particles will decrease, so that toner transfer can be maintained at a good level. Also, by increasing the maximum protrusion height, contact with the ink surface can be suppressed when performing the stamping rubbing evaluation described later, and rubbing does not occur, which is preferable. If it is 90 or less, contamination of the film surface and inside the device due to particle falling off can be suppressed, which is preferable. In one embodiment, the mass ratio of inorganic particles B1 to B2 is B1:B2=55:45 to 15:85. For example, the content of inorganic particles B2 may be greater than the content of inorganic particles B1, and the mass ratio of inorganic particles B1 to B2 may be B1:B2=15:85 or more.
[0038] The inorganic particles (B) may be surface-treated with an organic compound or a silicon compound having an organic portion in the molecule. In particular, when a non-aqueous medium is used, it is preferable to use inorganic particles (B) that have been surface-treated with an organic substance.
[0039] The inorganic particles (B) can be used in combination with organic particles, such as benzoguanamine particles, crosslinked polystyrene particles, and crosslinked acrylic particles.
[0040] The content of inorganic particles (B) in 100% by mass of the total solid content of the surface coating layer forming composition forming the surface coating layer is preferably 20% by mass or more and 40% by mass or less. More preferably, it is 21% by mass or more and 38% by mass or less. Even more preferably, it is 22% by mass or more and 36% by mass or less. When it is 20% by mass or more, the amount of inorganic particles that absorbs the printing ink is sufficient, and the evaluation of printing bleeding and printing rubbing is improved, which is preferable. A content of 21% by mass or more, or 22% by mass or more is preferable because it improves the printing performance. A content of 40% by mass or less is preferable because it reduces the amount of inorganic particles that scrape the toner layer, making toner transfer less likely to occur. A content of 40% by mass or less, or 38% by mass or less, or 36% by mass or less, is preferable because it more effectively suppresses toner transfer.
[0041] The inorganic particles (B) may be directly added to the coating material prepared by adjusting the binder composition (A), the functional composition (C) added as necessary, and the aqueous medium. For example, it is preferable to carry out a dispersion process after adding the inorganic particles in order to eliminate coarse inorganic particles and obtain a desired dispersed particle size. It is also more preferable to prepare a master batch of inorganic particles in order to obtain a desired dispersed particle size in a short time. For dispersing the inorganic particles, a ball mill, a sand mill, an attritor, a roll mill, an agitator, a colloid mill, an ultrasonic homogenizer, a homomixer, a dissolver, a pearl mill, a wet jet mill, a paint shaker, a butterfly mixer, a planetary mixer, a Henschel mixer, and the like can be mentioned. As the average particle size of the particles after dispersion, it is preferable that the 50% volume average diameter (Dv50) is 0.05 or more. If Dv50 is 0.05 μm or more, Ra and S do not become too small, which is preferable.
[0042] In addition to the binder composition (A), the surface coating layer forming composition can be used in combination with a functional composition (C). The effects of the functional composition (C) are not particularly limited, but examples of the effects include preventing particles from falling off the surface coating layer, preventing double feeding of films during printing, and improving liquid stability during processing.
[0043] For example, in order to prevent the particles from falling off the surface coating layer, slipperiness can be imparted to the particles so that local load is not applied to the particles. Examples of compositions having such functions include wax. The surface coating layer of the present invention preferably contains a wax component at 0 to 10.0% by mass. In addition to the above effects obtained by containing the wax component, it is also effective in reducing the static friction coefficient and suppressing toner transfer. Furthermore, if the wax component is 10.0% by mass or less, the particles are not covered too much, and bleeding or rubbing of the imprint can be maintained without being significantly affected. For example, the wax component can be contained at 0.5% by mass or more and 10.0% by mass or less. Examples of waxes include various ester waxes, low molecular weight polyolefins such as polyethylene, polypropylene, and polybutene, silicones that exhibit a softening point when heated, fatty acid amides such as oleic acid amide, erucic acid amide, ricinoleic acid amide, and stearic acid amide, vegetable waxes such as carnauba, rice wax, candelilla wax, Japan wax, and jojoba oil, animal waxes such as beeswax, mineral and petroleum waxes such as montan wax, ozokerite, ceresin, paraffin wax, microcrystalline wax, and Fischer-Tropsch wax, and modified versions of these waxes.
[0044] For example, in order to prevent double feeding of films during printing, antistatic properties can be provided to the surface coating layer in order to eliminate electrostatic adhesion between films. As a method for providing antistatic properties, a general coating type antistatic agent can be used as the functional composition (C). Examples of the antistatic agent include low molecular weight surfactant type antistatic agents, polymer type antistatic agents, etc. Examples of the low molecular weight surfactant type antistatic agents include cationic antistatic agents having cationic groups such as quaternary ammonium salts, pyridinium salts, and primary to tertiary amino groups, anionic antistatic agents having anionic groups such as sulfonate groups, sulfate ester groups, and phosphate ester groups, amphoteric antistatic agents such as amino acid antistatic agents and amino sulfate ester antistatic agents, and nonionic antistatic agents such as amino alcohol antistatic agents, glycerin antistatic agents, and polyethylene glycol antistatic agents. Examples of polymer-type antistatic agents include nonionic polymer-type antistatic agents such as polyethylene oxide, polypropylene oxide, polyethylene glycol, polyether ester amide, polyether ester, polyether polyolefin, and ethylene oxide-epichlorohydrin copolymers; anionic polymer-type antistatic agents such as polystyrene sulfonic acid; and cationic polymer-type antistatic agents such as quaternary ammonium base-containing acrylate polymers, quaternary ammonium base-containing styrene polymers, and quaternary ammonium base-containing polyethylene glycol methacrylate copolymers.
[0045] For example, in order to improve the liquid stability during processing, it is necessary to prevent the precipitation of particles dispersed in the liquid, and a particle dispersant can be used as the functional composition (C). By improving the liquid stability during processing, the surface coating layer can stably obtain the desired surface shape and performance, so it is preferable to use a particle dispersant.
[0046] The particle dispersant is not particularly limited, but an acrylic acid-based inorganic particle dispersant is preferred. The acrylic acid-based inorganic particle dispersant improves the stability of the liquid and provides the desired surface shape and performance.
[0047] The content of the dispersant is preferably 0.1% by mass or more and 1.5% by mass or less, based on 100% by mass of the total solid content of the surface coating layer forming composition forming the surface coating layer. More preferably, it is 0.3% by mass or more and 1.2% by mass or less. If it is contained at 0.1% by mass or more, the stability of the liquid is improved, which is preferable. If it is contained at 0.3% by mass or more, the stability of the liquid is further improved, which is more preferable. Furthermore, if it is contained at 1.5% by mass or less, it is preferable because there is no deterioration in toner fixation during printing. If it is contained at 1.2% by mass or less, it is preferable because there is no deterioration in imprinting performance in addition to the above performance.
[0048] The surface coating layer forming composition forming the surface coating layer may not contain the functional composition (C), but if it does, it is preferable to suppress the content to a level that does not interfere with the functions of the binder composition (A) and the inorganic particles (B). As a specific content, the content of the functional composition (C) is preferably 20% by mass or less in 100% by mass of the total solid content of the surface coating layer forming composition forming the surface coating layer. If it is within this range, it is preferable because it does not interfere with the functions of the binder composition (A) and the inorganic particles (B).
[0049] The binder composition (A) and the functional composition (C) can be used in any state of water-soluble, water-insoluble or water-based dispersion as long as the effect is not lost, but considering the dispersibility of inorganic particles described later, it is preferable to make the entire coating agent water-based, so it is preferable to use them in the state of water-soluble or water-based dispersion.When using in water-based, in addition to water, alcohols such as methanol, ethanol, isopropyl alcohol, and organic solvents in a range that does not inhibit the reactivity and solubility of the resin can be used as the solvent.
[0050] The functional composition (C) may be directly added to the coating liquid to be contained therein, or may be mixed into a master batch of the inorganic particles (B) to be contained in the coating liquid.
[0051] The coating agent containing the prepared binder composition (A), inorganic particles (B), and functional composition (C) can be applied onto the substrate film by the above-mentioned coating method, which is not particularly limited.
[0052] The drying and curing temperature after application is preferably 100°C or more and less than 200°C. At 100°C or more, insufficient drying and curing can be prevented, and blocking due to insufficient curing of the binder composition (A) can be prevented, so 100°C or more is preferable. At less than 200°C, the base film is less likely to shrink or deform due to heat, and can be dried while maintaining flatness, so less than 200°C is preferable. The drying and curing time is preferably 1 second or more and less than 180 seconds. At 1 second or more, insufficient drying can be prevented, and blocking due to insufficient curing of the binder composition (A) can be prevented, so 1 second or more is preferable. At less than 180 seconds, costs can be reduced from the viewpoint of productivity, so less than 180 seconds is preferable.
[0053] The thickness of the surface coating layer after drying and curing is preferably 5 to 35 μm. At 5 μm or more, the volume for absorbing the ink after imprinting can be secured, so 5 μm or more is preferable. At 35 μm or less, the strength of the surface coating layer can be maintained and powder falling off can be prevented, so 35 μm or less is preferable.
[0054] The surface-treated plastic film of the present invention has a static friction coefficient (μs) of 0.65 or less, more preferably 0.60 or less, when the surface coating layers are rubbed against each other. If it is within this range, friction is reduced when the film starts to move during work or transportation, and the occurrence of toner transfer is suppressed, which is preferable. Due to the nature of the friction coefficient, the dynamic friction coefficient is generally lower than the static friction coefficient. Due to this nature, if the static friction coefficient is below the above range, the dynamic friction coefficient is also below the above range, and toner transfer hardly occurs while the film is moving during work or transportation. The static friction coefficient (μs) is preferably 0.1 or more, for example, 0.2 or more, which is preferable because within this range, the occurrence of toner transfer can be suppressed and problems such as winding slippage are less likely to occur when processed into a film roll.
[0055] The surface roughness (Ra) of the surface coating layer is more than 1.6 μm and 4.0 μm or less. More preferably, it is 2.0 μm or more and 3.6 μm or less. By exceeding 1.6 μm, even if the inorganic particle (B) ratio is within the range of the present invention, for example, a relatively small content of 20 mass% or 25 mass%, small unevenness is formed on the surface, and the seal bleeding can be maintained in a good state. If it is 2.0 μm or more, the seal bleeding becomes in a very good state, which is more preferable. If it is 4.0 μm or less, the transferability of the seal ink is not deteriorated, which is preferable. If it is 3.6 μm or less, the transferability of the seal ink is further improved and legibility is improved, which is more preferable. Furthermore, by providing such surface roughness, the present invention can contribute to distinguishing the card from other types of plastic cards by touch.
[0056] The maximum projection height (Rz) of the surface coating layer is more than 20 μm and not more than 40 μm. In one embodiment, the maximum projection height (Rz) of the surface coating layer is 21 μm or more and 38 μm or less, for example, 23 μm or more and 37 μm or less. Within the above range, the printing blur is improved, the occurrence of toner transfer can be suppressed, and toner fixation is also improved. Furthermore, by having such a maximum projection height, the present invention can contribute to distinguishing it from other types of plastic cards by touch.
[0057] The surface roughness (Ra) and maximum projection height (Rz) of the present invention are both values measured in accordance with JIS B0601. μs can be controlled by the ratio of the binder composition to the inorganic particles, the ratio of the binder composition, the wax addition ratio, etc. Both Ra and Rz can be controlled by the type, average particle size, content, and type of binder composition of the inorganic particles used.
[0058] In this manner, the present invention provides the above-mentioned effects of excellent toner fixation, suppression of toner transfer, prevention of bleeding in printing applications, etc., by having a content of inorganic particles (B) of 20% by mass or more and 40% by mass or less based on 100% by mass of the total solids content of the surface coating layer forming composition, a static friction coefficient (μs) of 0.65 or less when the surface coating layers are rubbed against each other, a surface roughness (Ra) of more than 1.6 μm and less than 4.0 μm, and a maximum protrusion height (Rz) of more than 20 μm and less than 40 μm. Furthermore, because the present invention has such characteristics, it is possible to distinguish the surface-treated plastic film of the present invention from other types of plastic cards by touch. For example, even users with impaired eyesight, such as elderly people, can properly distinguish the surface-treated plastic film of the present invention by touch. On the other hand, as described above, the present invention can also reduce friction that occurs when the device starts moving during operation or transportation, thereby suppressing the occurrence of toner transfer. In this way, the present invention can achieve a good balance between toner fixability, tactile discrimination, and suppression of toner transfer by reducing friction.
[0059] The surface-treated plastic film of the present invention can be used for, for example, cards such as health insurance cards, qualification certificates, licenses, student ID cards, patient registration cards, and business cards, labels for business use, delivery slips, and recording paper for printers. EXAMPLES
[0060] The present invention will be described in detail below with reference to examples, but the present invention is not limited to the following examples. First, the evaluation methods and measurement methods used in the present invention will be described.
[0061] (1) Static friction coefficient, dynamic friction coefficient (μs, μd) In accordance with JIS K7125:1999 "Test method for coefficient of friction of plastic films and sheets," measurements were taken using a Tensilon (A&D, RTG-1210) with two identical film test pieces prepared and their surface coating layers rubbed against each other under a load of 4.4 kg.
[0062] (2) Surface roughness (Ra), maximum projection height (Rz) The measurements of Ra and Rz were made using a formula based on ISO4287:1997, and the arithmetic mean roughness and maximum projection height were measured, respectively. A laser microscope VK-X100 (Keyence Corporation) was used for the measurements, and the arithmetic mean roughness or maximum height within a 250μm x 250μm square was defined as one point, and four points were measured randomly, and the average value was taken as the surface roughness or maximum projection height (unit: μm).
[0063] (3) Dispersed particle size The dispersed particle size was measured as the 50% volume average size (Dv50) using a laser diffraction particle size distribution analyzer SALD-7500nano (Shimadzu Corporation). The master batch was diluted with ion-exchanged water to an absorbance of approximately 0.2, and measurements were performed using a high-concentration measurement unit. The refractive index was calculated by citing the refractive index of the type of inorganic particle with the highest mass percentage used from the database built into the device.
[0064] (4) Film thickness The thickness of the base film was measured at 10 points using a contact film thickness meter manufactured by Ono Sokki Co., Ltd., and the arithmetic average value was used as the film thickness. The thickness of the surface coating layer was measured at 10 points on the surface-treated plastic film after coating and drying using a contact film thickness meter to determine the arithmetic average value, and the difference between this and the thickness of the base film measured in advance was used.
[0065] (5) Toner transferability (toner transfer method A) An electrophotographic printer (495J Continuous Feed, manufactured by Fuji Xerox Co., Ltd.) was used to print on the surface coating layer, and then evaluation was performed using toner transfer method A. In toner transfer method A, two printed plastic films were cut to 9 cm x 5 cm, the printed surfaces were placed together, and the films were pinched at both ends with the fingers and bent up and down five times while still overlapping, and the degree of toner transfer to the opposite surface was visually judged. The criteria for toner transfer method B are as follows: ◎: No transfer at all ○: Slightly transferred in dots △: Transcribed, but the transcribed characters are unreadable ×: Transcribed and the transcribed characters can be read
[0066] (6) Toner transferability (Toner transfer method B) An electrophotographic printer (495J Continuous Feed, manufactured by Fuji Xerox Co., Ltd.) was used to print on the surface coating layer, and then evaluation was performed using the toner transfer method B. Toner transfer method B is a toner transfer evaluation method using a friction coefficient test method that conforms to JIS K7125:1999 "Test method for coefficient of friction of plastic film and sheet". Two identical film test pieces were prepared using a Tensilon (A&D, RTG-1210), and only one of the film test pieces was printed with the above printer. The printed surface coating layer and the non-printed surface coating layer were overlapped so that the printed film test piece was on the upper side, and measurements were performed with a load of 4.4 kg. The degree of transfer of the toner to the non-printed surface coating layer was judged visually. For visual evaluation, a mark was made at the position where the upper film was stationary before the measurement, and this position was expressed as the slip position. The criteria for judgment are shown below. ◎: No transfer at all ◯: Transferred only at the start of sliding, with slight dot-like transfer. No transfer occurred from other positions. △: Transferred only at the start of sliding, with slight linear transfer. No transfer occurred from other positions. ×: Slight linear transfer occurred at the sliding start position and other portions.
[0067] (7) Stamp bleeding A stamp was made on the surface coating layer using Shachihata Xstamper Name 9 (pigment ink: XLR-9N), and the print was left to stand for 5 minutes. The degree of bleeding of the letters was observed and judged according to the following criteria. ○: No bleeding occurs at all △: Blurring occurs, but the characters are legible ×: Difficulty in reading the characters
[0068] (8) Stamp wear The surface coating layer was stamped with Shachihata Xstamper Name 9 (pigment ink: XLR-9N) and left to stand for 30 seconds. The stamped area was then lightly rubbed with Kimwipe to observe how the letters had rubbed off, and the results were judged according to the following criteria. ○: No rubbing occurs △: Scratches occur, but the characters are legible ×: Difficulty in reading the characters
[0069] (9) Powder shedding The powder shedding was evaluated using a powder shedding Gakushin friction tester (manufactured by Yamaguchi Kagaku Sangyo Co., Ltd.) with a black backing paper (GA board-FS, Y-grain, manufactured by Takeo Co., Ltd.) at the contact point between the load head and the film, and the load on the head was set to 200gf / 25mm. 2 (5 mm x 5 mm) [0.0785 MPa], and the film was rubbed against the load head by reciprocating three times, after which the degree of whitening of the black mount was visually judged. 〇: The black backing paper was not whitened at all. △: Some whitening is observed on the black backing. ×: A lot of whitening is observed on the black backing paper.
[0070] (10) Texture The eyes were closed, the surface coating layer was rubbed with the index finger, and the texture was evaluated using the following sensory evaluation. The evaluation criteria were: CRISPER (registered trademark) K2323: Toyobo Co., Ltd., white polyester film containing voids, both sides treated for easy adhesion, apparent density 1.1 g / cm 3 , Ra=0.3 μm, Rz=7 μm (Ra, Rz, and S of both surfaces are substantially the same). ◯: It has a rough texture and is different from CRISPR (registered trademark) K2323. △: It has a slightly rough texture, and the difference from CRISPR (registered trademark) K2323 is clear. ×: Indistinguishable from CRISPR (registered trademark) K2323.
[0071] (11) Toner Fixation Electrophotographic copying machine (Fuji Xerox: C3376, cardboard 2: 170-256g / m 2 The toner was transferred and fixed onto the surface coating layer of the film using a pressure sensitive adhesive tape (Nichiban Co., Ltd.: Cellotape (registered trademark), 25 mm wide) which was firmly attached to the toner fixing surface, and then slowly peeled off at an angle of 90° to the film surface, and the remaining toner on the film was visually evaluated according to the following criteria. ○: Toner remaining on the surface coating layer of the film is 90% or more by area. △: Toner remaining on the surface coating layer of the film is 70% or more and less than 90% by area ×: Toner remaining on the surface coating layer of the film is less than 70% by area.
[0072] (Raw materials used) Binder Composition (A) A-1: Polyester resin (Vylonal (registered trademark) MD1200, manufactured by Toyobo Co., Ltd., solid content 34% by mass) A-2: Melamine resin (Amidea (registered trademark) M-3, manufactured by DIC Corporation, solid content 80% by mass) A-3: Urethane resin (Elastron (registered trademark) H-3DF, manufactured by Daiichi Kogyo Seiyaku Co., Ltd., solid content 27% by mass)
[0073] Inorganic particles (B) ·Inorganic particles B1 B-1: Calcium carbonate (Callite (registered trademark) KT, manufactured by Shiraishi Calcium Co., Ltd., average particle size 2.3 μm, solid content 100% by mass) B-2: Calcium carbonate (Callite (registered trademark) SA, manufactured by Shiraishi Calcium Co., Ltd., average particle size 3.3 μm, solid content 100% by mass) B-3: Calcium carbonate (Softon 2200, manufactured by Shiraishi Calcium Co., Ltd., average particle size 1.5 μm, solid content 100% by mass) B-4: Calcium carbonate (Brilliant (registered trademark)-15, manufactured by Shiraishi Calcium Co., Ltd., average particle size 0.15 μm, solid content 100% by mass) ·Inorganic particles B2 B-5: Silica (Silysia 470, manufactured by Fuji Silysia Chemical, average particle size 14.0 μm, solid content 100% by mass) B-6: Silica (Silysia 450, manufactured by Fuji Silysia Chemical, average particle size 8.0 μm, solid content 100% by mass) B-7: Silica (Silysia 440, manufactured by Fuji Silysia Chemical, average particle size 6.2 μm, solid content 100% by mass)
[0074] Functional composition (C) C-1: Liquid wax (Hitec E-9015, manufactured by Toho Chemical Industry Co., Ltd., solid content 40% by mass) C-2: Granular wax (Chemipearl (registered trademark) W310, manufactured by Mitsui Chemicals, Inc., solid content 40% by mass) C-3: Antistatic agent (EL Polymer WS-52R, manufactured by Shin-Nakamura Chemical Co., Ltd., solid content 10% by mass) C-4: Dispersant (Poise 521, Kao Corporation, solid content 40% by mass)
[0075] (Base film) Crisper (registered trademark) K2323: Toyobo Co., Ltd., white polyester film containing voids, treated for easy adhesion on both sides, apparent density 1.1 g / cm 3 , Ra=0.3μm, Rz=7μm, S=2μm (Ra, Rz, S of both surfaces are practically the same)
[0076] Example 1 (Preparation of Coating Layer-Forming Composition 1) A coating layer-forming composition 1 having the following composition was prepared. (Coating layer forming composition 1) Water 28.8 parts by mass Polyester resin A-1 46.6 parts by weight Calcium carbonate B-1 2.2 parts by mass Calcium carbonate B-5 4.1 parts by weight Liquid wax C-1 3.1 parts by weight Antistatic agent C-3 14.8 parts by weight Dispersant C-4 0.5 parts by weight
[0077] (Coating onto base film and drying) A 50 μm-thick polyester synthetic paper, Crisper K2323, was used as the base film, and the coating layer forming composition 1 was applied to the easy-adhesion surface of K2323 so that the coating layer thickness after drying would be 10 μm. The coating layer was then dried at 180° C. for 60 seconds to obtain the surface-treated plastic film described in Example 1.
[0078] (Examples 2 to 24, Comparative Examples 1 to 3) In Examples 2 to 24 and Comparative Examples 1 to 3, coating, drying and curing were carried out in the same manner as in Example 1, except that the surface coating layer forming compositions shown in Tables 1, 2 and 3 were changed, to obtain surface-treated plastic films. In Tables 1, 2, and 3, the composition ratios of the binder composition A, inorganic particles B, and functional composition C in the surface coating layer-forming composition are shown in parts by mass of each solid content when the total solid content ratio is taken as 100. In actual surface coating layer-forming compositions, water is added so that the solid content ratio of the entire liquid is 25%.
[0079] [Table 1]
[0080] [Table 2]
[0081] [Table 3]
[0082] Tables 4, 5, and 6 show the evaluation results of each of the examples and comparative examples.
[0083] [Table 4]
[0084] [Table 5]
[0085] [Table 6]
[0086] (Evaluation Results) Examples 1 to 23 used binder composition (A) and inorganic particles (B), and satisfied the following ranges: the content of inorganic particles (B) was 20% by mass or more and 40% by mass or less, the static friction coefficient was 0.65 or less, Ra was more than 1.6 and 4.0 μm or less, and Rz was more than 20 μm and 40 μm or less. The toner transferability, printability, powder falling, feel, and toner fixability were excellent. On the other hand, Comparative Example 1 does not contain inorganic particles (B), and Ra and Rz are outside the above ranges, so bleeding and rubbing occurred in the printability to the extent that the characters could not be read. In addition, when the texture was checked, it was impossible to distinguish it from K2323. In Comparative Example 2, the content of inorganic particles was 40 mass% or more, and the static friction coefficient was 0.65 or more, so the characters were at a level where they could be read in the toner transfer A method, and the transfer amount was particularly large in the toner transfer B method. Furthermore, powder falling of particles was confirmed in the powder falling property. In Comparative Example 3, Rz was less than 20.0 μm, so the printability was particularly deteriorated by rubbing, and the characters were not readable. In addition, the texture was also impossible to distinguish from K2323. [Industrial Applicability]
[0087] The surface plastic film of the present invention has good toner fixing properties, can be stamped, and does not cause toner transfer, so it can be suitably used for applications requiring toner printing, such as various labels, cards, delivery slips, and recording paper for printers.
Claims
1. A label, card, shipping slip, or printer recording paper having the following surface-treated plastic film: A surface-treated plastic film having a surface coating layer formed on at least one surface of a base plastic film, the surface coating layer is a layer formed by curing a surface coating layer-forming composition containing a binder composition (A) and inorganic particles (B); The content of the inorganic particles (B) in 100% by mass of the total solid content of the surface coating layer-forming composition is 20% by mass or more and 40% by mass or less, The static friction coefficient (μs) when the surface coating layers are rubbed against each other is 0.65 or less, The surface roughness (Ra) of the surface coating layer is more than 1.6 μm and not more than 4.0 μm, and the maximum projection height (Rz) is more than 20 μm and not more than 40 μm. Labels, cards, shipping slips or printer paper.
2. The surface-treated plastic film, 2. The label, card, delivery slip, or recording paper for a printer according to claim 1, wherein the surface coating layer forming composition for forming the surface coating layer contains a wax component as an additive in an amount of 0 mass % or more and 10.0 mass % or less of the total solid content.
3. The label, card, delivery slip, or recording paper for a printer as described in claim 1, wherein, in the surface-treated plastic film, the binder composition (A) contains at least a polyester resin, and the content of the polyester resin in 100% by weight of the total solid content of the binder composition (A) is 25% by mass or more and 100% by mass or less.
4. In the surface-treated plastic film, the inorganic particles (B) include at least particles (B1) having an average particle diameter of 0.1 μm or more and less than 5.0 μm and particles (B2) having an average particle diameter of 5.0 μm or more and 20.0 μm or less, The label, card, delivery slip, or printer recording paper according to claim 1, wherein B1:B2=60:40 to 10:90 (mass ratio).
5. A label, card, delivery slip or printer recording paper as described in claim 1, wherein, in the surface-treated plastic film, the base plastic film is a white polyester film containing cavities.
6. The label, card, delivery slip or recording paper for a printer as described in claim 1, wherein, in the surface-treated plastic film, the base plastic film is a polyester film or a white polyester film containing voids, and the polyester resin made from recycled raw materials such as film scraps and PET bottles accounts for 25% by mass or more and 90% by mass or less of the total polyester resin constituting the polyester film or the white polyester film containing voids.
Citation Information
Patent Citations
Printed coated metal sheet excellent in slip resistance and wear resistance
JP2000273654A
Surface-treated plastic film
JP2020019893A
Sealing sheet for solar cell
US20140360573A1
Material to be recorded for toner printing
JP2003345051A